2000
DOI: 10.1084/jem.192.11.1553
|View full text |Cite
|
Sign up to set email alerts
|

Cxc Chemokine Receptor 5 Expression Defines Follicular Homing T Cells with B Cell Helper Function

Abstract: Leukocyte traffic through secondary lymphoid tissues is finely tuned by chemokines. We have studied the functional properties of a human T cell subset marked by the expression of CXC chemokine receptor 5 (CXCR5). Memory but not naive T cells from tonsils are CXCR5+ and migrate in response to the B cell–attracting chemokine 1 (BCA-1), which is selectively expressed by reticular cells and blood vessels within B cell follicles. Tonsillar CXCR5+ T cells do not respond to other chemokines present in secondary lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
958
4
16

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,100 publications
(1,016 citation statements)
references
References 50 publications
38
958
4
16
Order By: Relevance
“…found that the number of antigen‐specific memory cells that expressed Tfh markers declined over time, suggesting that Tfh cells fail to differentiate into long‐lived memory cells 57. However, we and others have shown that both mouse and human CXCR5+ memory CD4 T‐cells provide rapid assistance to B‐cells upon reactivation 61, 62, 63, 64, 65, 66, 67, 68, 69. Importantly, Alexander et al .…”
Section: Memory Cd4 T‐cells Are Found Throughout the Bodymentioning
confidence: 74%
“…found that the number of antigen‐specific memory cells that expressed Tfh markers declined over time, suggesting that Tfh cells fail to differentiate into long‐lived memory cells 57. However, we and others have shown that both mouse and human CXCR5+ memory CD4 T‐cells provide rapid assistance to B‐cells upon reactivation 61, 62, 63, 64, 65, 66, 67, 68, 69. Importantly, Alexander et al .…”
Section: Memory Cd4 T‐cells Are Found Throughout the Bodymentioning
confidence: 74%
“…As CD4 + T cells differentiate into pre‐Tfh cells they downregulate expression of C‐C chemokine receptor type 7 (CCR7) and P‐selectin glycoprotein ligand 1 (PSGL‐1), which promote localization to and retention within the T‐cell zone, and upregulate expression of the chemokine receptor characteristic of Tfh cells, C‐X‐C chemokine receptor type 5 (CXCR5), which binds C‐X‐C motif chemokine ligand 13 (CXCL13), a chemokine produced in B‐cell follicles 131, 132. This enables pre‐Tfh cells to migrate to the margin of the B‐cell follicle,133 where they interact with B cells and the next step in Tfh differentiation takes place.…”
Section: T Follicular Helper Cells and Their Role In Bnab Inductionmentioning
confidence: 99%
“…The differentiation of these long‐lived B cells is linked to the differentiation of follicular T helper (Tfh) cells, a subset of CD4 + T cells that is specialized in providing help to B cells in the germinal center (GC) reaction (Breitfeld et al , 2000; Schaerli et al , 2000). …”
Section: Introductionmentioning
confidence: 99%